ナンキョク ナイリク ヒョウショウジョウ ヘ コウカ タイセキ スル ブッシツ ニツイテ - 神山, 孝吉; カミヤマ, コウキチ; 渡辺, 興亜; ワタナベ, コウア; Kamiyama, Kokichi; Watanabe, Okitsugu (1994)
P(論文) さまざまな物質が南極内陸部上空に運ばれ, 雪面上に蓄積している。内陸部の降雪・積雪の化学組成は, 大気中の内陸部への物質輸送過程と内陸部大気中の物質の存在量を反映している。いくつかの物質濃度は内陸部の降雪で増加傾向にあり, 南極内陸部は特異な堆積環境の下にあることを示唆している。なぜなら広大な雪面の続く内陸は, 物質の供給源から隔たっており, 降雪中の一部物質濃度の増加は単純には説明できないからである。本報告では, 南極氷床内陸部に堆積する降雪・積雪の化学組成についての研究を概観し, 内陸積雪の化学的性質の特異性を指摘する。すなわち積雪中のトリチウムなどに代表されるようにいくつかの物質濃度が内陸内部で増加している。南極内陸部では大気が著しい低温を示すという地域的な要因に, 成層圏を通して遠隔地域からの物質輸送過程が存在し地球規模での物質循環過程を反映するという要因が加わって, 内陸部の特異性を生みだしていると考えられる。南極内陸部の積雪の化学的特異性を考慮することによって, 雪氷コアを通して地球環境を探る研究はさらに有効になると思われる。 Various substances are transported over the inland plateau of Antarctica through the atmosphere, and deposited onto the snow surface. The chemical composition of the snow will reflect the transportation process and the amounts of the substances present in the atmospheric environment. Concentrations of some substances show an increasing trend due to interior continental snowfall, suggesting that the interior of the Antarctic continent is under a unique sedimentation environment. This is because the inland plateau, a large continuous snow area, is a long way from the area where the substances in the atmosphere are originating, and there is no simple explanation for the increase in concentration of some of the substances in the falling snow. In this report, the investigations on the snow chemistry on the inland plateau, Antarctica, are briefly reviewed. The concentrations of some substances in snow, for example tritium, have increased on the inland plateau. This was produced both by the local effect over the inland plateau, caused by the extremely low temperature air mass, and by the global circulation through the stratosphere, which transports substances directly from remote areas. By considering the special chemical features of the accumulated snow in the interior of the Antarctic continent, we can more effectively interpret ice and snow cores in our study of the global atmospheric environment. departmental bulletin paper